2019
DOI: 10.1038/s41597-019-0170-y
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on equine cartilage near infrared spectra, composition, and functional properties

Abstract: Near infrared (NIR) spectroscopy is a well-established technique that is widely employed in agriculture, chemometrics, and pharmaceutical engineering. Recently, the technique has shown potential in clinical orthopaedic applications, for example, assisting in the diagnosis of various knee-related diseases ( e . g ., osteoarthritis) and their pathologies. NIR spectroscopy (NIRS) could be especially useful for determining the integrity and condition of articular carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…characterization techniques, including infrared 16 and nearinfrared spectroscopy, 17 second harmonic generation 18 and Raman spectroscopy, 19 can be used to probe the cartilage ECM. However, all these techniques can only probe changes in a semi-quantitative way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…characterization techniques, including infrared 16 and nearinfrared spectroscopy, 17 second harmonic generation 18 and Raman spectroscopy, 19 can be used to probe the cartilage ECM. However, all these techniques can only probe changes in a semi-quantitative way.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, common procedures are based on biochemical methods, which require the digestion of the tissue, so that the global supramolecular structure is not preserved. As an alternative, immunohistology, or other label-free characterization techniques, including infrared 16 and near-infrared spectroscopy, 17 second harmonic generation 18 and Raman spectroscopy, 19 can be used to probe the cartilage ECM. However, all these techniques can only probe changes in a semi-quantitative way.…”
Section: Introductionmentioning
confidence: 99%
“…Their study indicated that the SVM model can distinguish anterior cruciate ligament transection (ACLT) from non-operationally operated control (CNTRL) samples, the DNN model can discriminate between different types of OA, and LR can differentiate between contralateral (CL) and CNTRL samples. NIR spectroscopy, in combination with machine learning techniques, can provide a powerful tool for the classification of cartilage integrity [ 71 ], with the potential to accurately distinguish between normal and early osteoarthritic cartilage [ 72 , 73 ].…”
Section: Nir Spectroscopymentioning
confidence: 99%
“…This data set 3 contains NIR spectroscopy measurements (functional predictor X) within the spectrum region of 700-1050 nm from 869 different locations across the articular surfaces of five equine fetlock joints, paired with comprehensive reference measurements from biomechanics, chemical composition and internal structure of the tissue, such as, instantaneous moduli (Y ), collagen contents (Z 1 ), proteoglycan contents (Z 2 ), cartilage thickness (Z 3 ), and calcified layer thickness (Z 4 ), etc. More details are available [30]. The sample data with size 530 were retained after removing all incomplete records.…”
Section: Equine Articular Cartilage Data Setmentioning
confidence: 99%